The application of the Johns Hopkins Hospital Template on urine cytology. Issue 8 (26th February 2015) - Wu, Howard H.; Redelman, Megan; Chen, Shaoxiong; Grignon, David J.; Cramer, Harvey M.
<x xml:space="preserve">Abstract</x> Background To evaluate the utility of the Johns Hopkins Hospital (JHH) template in detection of high‐grade urothelial carcinoma (HGUC). Methods A computerized search of our laboratory information system was performed for all urine cytology cases from 2009 to 2011 processed by the SurePath™. We included only cases with correlating surgical pathology within 6 months after the urinary samples were obtained. The original cytologic diagnoses were reclassified according to the JHH template, and these cytolog ic diagnoses were then correlated with the follow‐up surgical pathology diagnoses. Results A total of 273 urine samples with histopathologic follow‐up were identified. The reclassified cytologic diagnoses included negative for urothelial atypia or malignancy (NUAM) 110; atypical urothelial cells of undetermined significance (AUC‐US) 83; atypical urothelial cells, cannot exclude high‐grade urothelial carcinoma (AUC‐H) 49; HGUC 29; and low‐grade urothelial carcinoma (LGUC) 2. More than one‐half of patients (58%) who had biopsy‐confirmed high‐grade urothelial lesions had a preceding cytologic diagnosis of AUC‐H or HGUC. AUC‐H and HGUC are associated with high‐grade urothelial lesions in 80% and 90% of the cases and show statistical significance when compared with AUC‐US or NUAM (P < 0.05). Conclusion The JHH template is useful and effective in identifying patients with high‐grade urothelial lesions who need to undergo cystoscopy. Diagn. Cytopathol. 2015;43:593–597. © 2015 Wiley Periodicals, Inc.